(untitled) (Scientific journal of the Fergana State University, 2025)
This scientific article investigates the personality of Amir Shohmurod, the third representative of the Manghit dynasty, and his activities as a statesman, as well as how he lived according to the laws of Sharia, as presented by researchers.